2019
DOI: 10.1080/08927936.2019.1621520
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Decision Making in the Process of Acquiring a Dog

Abstract: To prevent potential problems in the relationship between people and their dogs, it is important to engage in a thoughtful decision-making process with regard to acquiring a dog. To map the most important elements in the decision-making process, a social cognitive model was applied using seven psychological constructs: perceived advantages of having a dog; perceived disadvantages; the social norm; self-efficacy; optimism; expected commitment; and the intention to acquire a dog. People who were planning to acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This study only assessed the experiences of adults, although past research in the UK has shown sociodemographic differences in pet ownership in children and adolescents (Miles et al, 2017;Westgarth et al, 2010). Finally, we only assessed current pet ownership and were not able to explore duration of pet relationships, history of pet ownership, or timing and reasons for acquisition of a pet, which can also be related to demographic variables (Vink, Dijkstra, & Epstude, 2019). These relationships should be explored with robust qualitative and mixed methods research.…”
Section: Limitationsmentioning
confidence: 99%
“…This study only assessed the experiences of adults, although past research in the UK has shown sociodemographic differences in pet ownership in children and adolescents (Miles et al, 2017;Westgarth et al, 2010). Finally, we only assessed current pet ownership and were not able to explore duration of pet relationships, history of pet ownership, or timing and reasons for acquisition of a pet, which can also be related to demographic variables (Vink, Dijkstra, & Epstude, 2019). These relationships should be explored with robust qualitative and mixed methods research.…”
Section: Limitationsmentioning
confidence: 99%
“…To understand the psychology of this relationship's development, the owner's perceptions (e.g., advantages and disadvantages) needs to be understood since these perceptions influence owners' feelings and behaviors towards their dogs. Perceptions are based on experience, learning from others, and comparing oneself to others, and can be conceptualized as social cognitive determinants [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The social-cognitive factors involved in decision-making are described in the Theory of Planned Behavior (Ajzen, 1991). In a previous study (Vink, Dijkstra, & Epstude, 2019), we demonstrate that certain aspects of the decision-making process at time zero (T0) are related to the actual acquisition of a dog (T1; yes/no). In the present study, we examine how aspects of the decision-making process at T0 are related to canine behavior problems and owner satisfaction, as measured in two follow-up questionnaires, six (T1) and 18 months (T2) after acquiring a dog.…”
mentioning
confidence: 73%